A Pragmatic Analysis of Impoliteness Strategies in Selected English Political Caricatures - Mohammed Ali Mala Hassan; Kavi Shakir Mohammed (Zanco Journal of Humanity Sciences)
The study investigates the pragmatic use of Culpeper’s (1996) impoliteness strategies in the selected English political caricatures. Although caricatures deliver political messages, the expressions of impoliteness can differ between cultures. Therefore, a single caricature may employ more than one impoliteness strategy. A mixed approach, combining both qualitative and quantitative methods, is utilized in the study. The data is collected from the caricatures of famous English caricaturists, whose work has been published on the X platform. The findings show that four impoliteness strategies are observed in the selected political caricatures. The analysis of the selected data shows that among the impoliteness strategies, bald on record impoliteness is the most frequently used, and negative impoliteness is the second most used. Positive impoliteness and mock politeness together rank third, while there is no occurrence of withholding politeness in the selected English political caricatures.